2000
DOI: 10.1021/ol006096j
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Dependent Stabilization of the E Configuration of Propargylic Secondary Amides

Abstract: Secondary amides typically exist 98-99% in the Z rotamer to avoid steric repulsion between the substituent on the carbonyl carbon and the nitrogen. In contrast, secondary amide 3a displays 24% E rotamer at room temperature in aqueous solution. The analogous ester displays 6% E rotamer in chloroform, which suggests that the relatively high E conformer population observed for 3a in water results in part from the low steric bulk of the sp-hybridized carbons and in part from the hydrophobic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 8 publications
4
51
0
Order By: Relevance
“…The flat geometry of aromatic rings is traditionally considered hydrophobic. The aromatic–aromatic interaction could also be a result of desolvation, also known as classical hydrophobic effect, in which the hydrophobic surface area of amitriptyline exposed to the polar solvent is minimized upon aromatic stacking 22. This is consistent with the work by Cubberley et al20 They reported the higher association constant in a more polar solvent and concluded that the association between electron‐rich and electron‐deficient monomers was driven primarily by hydrophobic interaction.…”
Section: Resultssupporting
confidence: 84%
“…The flat geometry of aromatic rings is traditionally considered hydrophobic. The aromatic–aromatic interaction could also be a result of desolvation, also known as classical hydrophobic effect, in which the hydrophobic surface area of amitriptyline exposed to the polar solvent is minimized upon aromatic stacking 22. This is consistent with the work by Cubberley et al20 They reported the higher association constant in a more polar solvent and concluded that the association between electron‐rich and electron‐deficient monomers was driven primarily by hydrophobic interaction.…”
Section: Resultssupporting
confidence: 84%
“…To study the interconvertion phenomenon, variable temperature 1 H NMR analyses were undertaken [33] in the temperature range from 298 K to 363 K and the spectrum is given in Figure 6. At room temperature (298 K), the resonances for both E and Z isomers are well distinguishable.…”
Section: Isomeric Investigation Of Hl By Variable Temperature Nmrmentioning
confidence: 99%
“…The 1 H NMR spectrum of ACINH in DMSO-d 6 show double set of signals for C(4)H, C(12)H and NH protons due to existence of ACINH in two isomeric forms arising due to the rotation along C-C (C3-C11) single bond [4][5][6]. Thus tentatively s-trans and s-cis isomer can be predicted for ACINH (Scheme 2).…”
Section: Nmr Studiesmentioning
confidence: 99%
“…Hydrazones distinguished by the presence of two interlinked nitrogen atoms R 1 C N-NR 2 are interesting, because they can function as antimicrobial, antitubercular and antitumor agents [1][2][3]. The structural flexibility of hydrazones allows them to exhibit amido-imidol tautomerism and they can also exist in different isomeric forms arising due to free rotation around C-C or N-N single bonds around azomethine framework [4][5][6]. Chemistry of transition metal complexes with such multidentate Schiff base ligands is fascinating because these metal ions exhibit different oxidation states [7].…”
Section: Introductionmentioning
confidence: 99%